2018
DOI: 10.5194/acp-18-7815-2018
|View full text |Cite
|
Sign up to set email alerts
|

Radiative absorption enhancement of dust mixed with anthropogenic pollution over East Asia

Abstract: Abstract. The particle mixing state plays a significant yet poorly quantified role in aerosol radiative forcing, especially for the mixing of dust (mineral absorbing) and anthropogenic pollution (black carbon absorbing) over East Asia. We have investigated the absorption enhancement of mixed-type aerosols over East Asia by using the Aerosol Robotic Network observations and radiative transfer model calculations. The mixed-type aerosols exhibit significantly enhanced absorbing ability than the corresponding unmi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 74 publications
4
39
0
Order By: Relevance
“…This is because the MERRA-2 emission inventories of aerosols species have not been updated since the mid-2000s (Randles et al, 2017). Moreover, recent modeling studies have suggested that the mixing state and aging processes can largely change the aerosol lifetime during simulation, and consequently affect the amount of aerosols lifted to UTLS, and some optical measurements further support the result that dust aerosol can be coated by anthropogenic aerosols over east Asia and then significantly enhance absorbing ability Tian et al, 2018). Nonetheless, our findings provide a working hypothesis that warrants further investigations using both modeling and observational studies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This is because the MERRA-2 emission inventories of aerosols species have not been updated since the mid-2000s (Randles et al, 2017). Moreover, recent modeling studies have suggested that the mixing state and aging processes can largely change the aerosol lifetime during simulation, and consequently affect the amount of aerosols lifted to UTLS, and some optical measurements further support the result that dust aerosol can be coated by anthropogenic aerosols over east Asia and then significantly enhance absorbing ability Tian et al, 2018). Nonetheless, our findings provide a working hypothesis that warrants further investigations using both modeling and observational studies.…”
Section: Discussionsupporting
confidence: 65%
“…This could be related to a warming trend of the land surface over northern India and the desert regions to the west (Jin and Wang, 2017). A warmer and drier land surface before monsoon onset is likely to favor increased biomass burning emissions (van der Werf et al, 2006) (Fig. S5).…”
Section: Long-term Trendsmentioning
confidence: 99%
“…In Case I, the irregular dust particles with high vertical depolarization ratio mainly concentrated near the ground (below 480 m) and contributed more to the overall β in this area. This suggests that dust was generated locally [59,60]. Within the same range of RH, the backscattering coefficient of the non-dust particles increased faster than the total backscattering coefficient.…”
Section: Isolating Non-dust Fine-mode Aerosol Hygroscopic Propertiesmentioning
confidence: 94%
“…Remote Sens. 2020, 11, x; doi: FOR PEER REVIEW www.mdpi.com/journal/remotesensing [59,60]. Within the same range of RH, the backscattering coefficient of the non-dust particles increased faster than the total backscattering coefficient.…”
Section: Isolating Non-dust Fine-mode Aerosol Hygroscopic Propertiesmentioning
confidence: 99%
“…In contrast, less developed areas with smaller populations across the Tibetan Plateau and eastern Inner Mongolia constituted the low AOD centers. In addition to natural dust aerosols, aerosols emitted by anthropogenic activities, such as smoke particles from burning of agricultural biomass, sulphate and black and organic carbon aerosols from industrial activities could be responsible for enhanced levels of aerosol loadings during DJF over the SC with a high AOD value of 0.88 [38][39][40].…”
Section: Seasonal Distribution Of Aod and The Percentage Of D_aod To mentioning
confidence: 99%